Integrating Social Rehabilitation into the Education System for Adolescent Drug Addicts: Legal Framework, Potential, and Challenges - Alhakim, Abdurrakhman; Anakotta, Marthsian Yeksi; Febriyani, Emiliya; Tan, Winsherly (Universitas Lampung, 2024)
Despite importance of education in overcoming drug addiction, the connection between the education system and the juvenile justice system remains unclear. Juvenile drug addicts often experience socially-disadvantaged situation, thereby social rehabilitation is an important aspect of recovery aside from medical rehabilitation. This research was performed to identify the challenges in social reintegration among juvenile drug addicts, describe the legal interplay between the relevant framework, and propose a model of legal development for the integration of social rehabilitation for juvenile drug addicts into the education system. Using normative legal research method and statutory approach, this research revealed numerous potentials and challenges in integrating social rehabilitation into the education system. A model consisting of normative reforms and practical framework of works is proposed to be applied by educational institutions and relevant government agencies. This research offers a vital step toward creating inclusive educational environments that prevent relapse and foster societal integration.